The Effect of Organizational Culture, Competence and Motivation on the SMEs Performance in the Covid-19 Post Pandemic and Digital Era - Nurhayati Haris; Jamaluddin Jamaluddin; Ernawaty Usman (Journal of Industrial Engineering & Management Research, 2023)
The purpose of this study was to analyze the influence of employee work culture on employee performance, the effect of work motivation on performance and the effect of competence on employee performance in the Covid-19 post pandemic and digital era. This research method is a quantitative method with a survey, the respondents to this study were 390 SMEs owners who were selected by simple random sampling. The research data was obtained by distributing online questionnaires via social media. The questionnaire was designed using a Liker scale of 1 to 7. Analysis of research data used structural equation modeling (SEM) with the SmartPLS 3.0 software data processing tool. The stages of data processing are validity, reliability and hypothesis testing. The variables to be examined are work culture, motivation and competence as independent variables and performance as the dependent variable. The results of the research hypothesis test show that work culture has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, and competence has a positive and significant effect on employee performance in the Covid-19 post pandemic and digital era.